2022
DOI: 10.1038/s41389-022-00395-6
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Inducible Kinase 1 is a potential therapeutic target in Desmoplastic Small Round Cell Tumor

Abstract: Desmoplastic Small Round Cell Tumor (DSRCT) is a rare and aggressive malignant cancer caused by a chromosomal translocation t(11;22)(p13;q12) that produces an oncogenic transcription factor, EWSR1-WT1. EWSR1-WT1 is essential for the initiation and progression of DSRCT. However, the precise mechanism by which EWSR1-WT1 drives DSRCT oncogenesis remains unresolved. Through our integrative gene expression analysis, we identified Salt Inducible Kinase 1 (SIK1) as a direct target of EWSR1-WT1. SIK1 as a member of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Similarly, fusion protein expression via Western blot showed increased expression in sphere versus adherent cells (Figure 6B). To determine whether EWSR1-WT1 is necessary for tumorsphere formation, we employed our previously established doxycycline (dox)-inducible EWSR1-WT1 knockdown system that utilizes shRNA targeting the 3′ UTR of WT1 to reduce fusion gene expression (Hartono et al, 2022). Because native WT1 is not expressed in DSRCT, shRNA targeting the 3′ UTR of WT1 specifically silences the EWSR1-WT1 fusion gene without a concern for WT1 off-target effects (Hingorani et al, 2020).…”
Section: Ewsr1-wt1 Is Essential For the Desmoplastic Small Round Cell...mentioning
confidence: 99%
“…Similarly, fusion protein expression via Western blot showed increased expression in sphere versus adherent cells (Figure 6B). To determine whether EWSR1-WT1 is necessary for tumorsphere formation, we employed our previously established doxycycline (dox)-inducible EWSR1-WT1 knockdown system that utilizes shRNA targeting the 3′ UTR of WT1 to reduce fusion gene expression (Hartono et al, 2022). Because native WT1 is not expressed in DSRCT, shRNA targeting the 3′ UTR of WT1 specifically silences the EWSR1-WT1 fusion gene without a concern for WT1 off-target effects (Hingorani et al, 2020).…”
Section: Ewsr1-wt1 Is Essential For the Desmoplastic Small Round Cell...mentioning
confidence: 99%
“…The hg38 build contains an erroneously duplicated region, which includes paralogous genes SIK1 and SIK1B; the hg38-specific gene SIK1 has been linked to developmental and epileptic encephalopathy 39 . These two genes are identical except for a segment of the sequence encoding for a single amino acid 40 . In correcting this duplication, the CHM13 annotation used the SIK1B version of the gene.…”
Section: Resultsmentioning
confidence: 99%
“…SIK1B had higher expression in CHM13 in all biospecimen types (5.5x-8.5x) compared to hg38, likely due to the removal of SIK1 which was siphoning reads in the hg38 alignment ( Figure 2d ). SIK1B is oncogenic, and further studies should be done to reveal if SIK1B is also associated with development and epileptic encephalopathy 40 . Given the transcriptomic impact of this false duplication in hg38, we suggest using CHM13 for assessment of the SIK1/SIK1B locus.…”
Section: Resultsmentioning
confidence: 99%
“…One potential explanation for the importance of AR could be that it acts as a critical downstream effector of the EWSR1::WT1 fusion protein. Utilizing previously established doxycycline (dox)-inducible cell lines that knockdown the expression of EWSR1::WT1 17 , we examined the role of the fusion protein in AR expression. EWSR1::WT1 knockdown led to reductions in AR at the protein level (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…identified three prostate cancer cell lines that lack AR expression but still were sensitive to enzalutamide treatment as a result of the glucocorticoid receptor 30 . Likewise, in breast cancer, cytotoxic effects of enzalutamide have been shown to be independent of AR and instead reliant on targeting the estrogen receptor 17 . Intriguingly, we found that treatment with 10µM of enzalutamide reduced EWSR1::WT1 expression, which could explain its cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%